2005
DOI: 10.1111/j.1348-0421.2005.tb03664.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Soluble Form (Gs) of Rabies Virus Glycoprotein (G): Molecular Structure of Gs Protein and Possible Mechanism of the Shedding

Abstract: In this study, we investigated the antigenic structures and maturation of some C‐terminal‐deficient derivatives of rabies virus glycoprotein (G). The Gs protein, a soluble form of G protein shed from infected cells, displayed antigenicity to most of our conformational epitope‐specific anti‐G mAbs, but took the 1‐30‐44 epitope‐deficient conformation (termed GC form). (The 1‐30‐44 epitope was acid‐sensitive and dependent on two separate regions, the Lys‐202‐containing and Asn‐336‐containing regions; Kankanamge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Further investigation by the team revealed that symptoms were seen on 25th September, 2012. Humans can begin to shed rabies virus in saliva and tears 2 weeks before onset of symptoms [10]. The patient was therefore considered to be potentially infectious during September 11th - 29th, the period from 2 weeks before onset of symptoms until his death.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation by the team revealed that symptoms were seen on 25th September, 2012. Humans can begin to shed rabies virus in saliva and tears 2 weeks before onset of symptoms [10]. The patient was therefore considered to be potentially infectious during September 11th - 29th, the period from 2 weeks before onset of symptoms until his death.…”
Section: Resultsmentioning
confidence: 99%
“…The viral shedding period is known in dogs, cats, and ferrets, and is usually three to seven days before onset of clinical manifestations of rabies and throughout the course of the disease. Longer shedding periods of 10-14 days prior to the onset of symptoms have been observed with certain canine rabies virus variants in experimental infections, but these are the exception [ 8 ]. Viral excretion in other animals is highly variable, for example, in one study in bats viral shedding for 12 days before evidence of illness was documented[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…α7 and α4β2 nAChRs are expressed along axons, dendrites, and cell bodies, in addition to pre- and post-synaptic locations ( Zarei et al., 1999 ; Jones and Wonnacott, 2004 ; Zhong et al., 2008 ). A soluble form of RVG, which lacks the C-terminal anchoring region of the glycoprotein, has been detected in the media of rabies-infected cultured cells ( Morimoto et al., 1993 ; Thirapanmethee et al., 2005 ). As the hippocampal synaptic cleft (~20 nm ( Schikorski and Stevens, 1997 )) is too small to accommodate the rabies virion (60 x 180 nm ( Rupprecht, 1996 )), it is likely that soluble RVGs, if these are produced in vivo , target pre- and post-synaptic α7 nAChRs within the hippocampus ( Fabian-Fine et al., 2001b ).…”
Section: Discussionmentioning
confidence: 99%